2020
DOI: 10.1186/s12974-019-1693-z
|View full text |Cite
|
Sign up to set email alerts
|

Dectin-1/Syk signaling triggers neuroinflammation after ischemic stroke in mice

Abstract: Background: Dendritic cell-associated C-type lectin-1 (Dectin-1) receptor has been reported to be involved in neuroinflammation in Alzheimer's disease and traumatic brain injury. The present study was designed to investigate the role of Dectin-1 and its downstream target spleen tyrosine kinase (Syk) in early brain injury after ischemic stroke using a focal cortex ischemic stroke model. Methods: Adult male C57BL/6 J mice were subjected to a cerebral focal ischemia model of ischemic stroke. The neurological scor… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
66
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 83 publications
(71 citation statements)
references
References 62 publications
(61 reference statements)
2
66
0
Order By: Relevance
“…However, these studies were performed in BV2 microglial cells which suggests there may be differences that are cell line specific ( Baldwin et al, 2015 ). Dectin-1 is involved in neuroinflammation and secretory cellular processes and should be affected by cocaine administration ( Baldwin et al, 2015 ; Gensel et al, 2015 ; Ye et al, 2020 ). We demonstrated there was a decrease as predicted in the dectin-1 levels.…”
Section: Discussionmentioning
confidence: 99%
“…However, these studies were performed in BV2 microglial cells which suggests there may be differences that are cell line specific ( Baldwin et al, 2015 ). Dectin-1 is involved in neuroinflammation and secretory cellular processes and should be affected by cocaine administration ( Baldwin et al, 2015 ; Gensel et al, 2015 ; Ye et al, 2020 ). We demonstrated there was a decrease as predicted in the dectin-1 levels.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that we only used male mice in this study in order to avoid the effect of sex hormone ( Spychala et al, 2018 ; Zhang H. et al, 2018 ; Otxoa-de-Amezaga et al, 2019 ; Xu et al, 2019 ; Al Mamun et al, 2020 ; Ye et al, 2020 ). It has been reported that estrogen receptors (ERs) are widely distributed in the brain, present on both neurons and glia, and expressed by both sexes ( Rettberg et al, 2014 ; Hewitt and Korach, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the hyperacute phase of AIS, we observed a positive correlation between ficolin-3, MAP-1, MBL and the NO donor L-arginine reflecting the protective role of L-arginine presumably by improving the cerebral microcirculation in a prothrombotic environment induced by complement activation. 25 Beside initiating activation of complement via the lectin pathway, ficolins may trigger activation of the immune system by production of nitric oxide (NO) by macrophages, thus limiting the infection and concurrently orchestrating the subsequent adaptive immune response. 26 In acute coronary syndrome, the kinetics of oxidized lowdensity lipoprotein receptor-1 (LOX-1), a lectin like molecule, was described with an acute increase up to 12 postevent hour and a subsequent decrease, while NOx derived from the L-arginine-nitric oxide pathway, decreased promptly suggesting an impaired NO metabolism during acute ischemic coronary event.…”
Section: Discussionmentioning
confidence: 99%